Facade of Club of St Anthony - Mumbai Archive Project (Jio Institute, 2024)
Kudd is a dormitory-style club that provides affordable accommodation to Goan residents living and working in Mumbai. From 1960 onwards, after the integration of Goa with India, outward migration from Goa has considerably declined. Dwindling occupancy impacted the operation of kudds. Many kudds closed or were repurposed. Among the handful of operational kudds is the Club of St. Anthony in Mazagaon.